Bureaucracy, work and violence : the Reich Ministry of Labour in Nazi Germany, 1933-1945 - Nützenadel, Alexander 1965- HerausgeberIn; Skinner, Alex ÜbersetzerIn; Unabhängige Historikerkommission zur Geschichte des Reichsarbeitsministeriums 1933-1945 (Berghahn Books, 2020)
"Work played a central role in Nazi ideology and propaganda, and even today there remain some who still emphasize the supposedly positive aspects of the regime's labor policies, ignoring the horrific and inhumane conditions they produced. This definitive volume provides, for the first time, a systematic study of the Reich Ministry of Labor and its implementation of National Socialist work doctrine. In detailed and illuminating chapters, contributors scrutinize political maneuvering, ministerial operations, relations between party and administration, and individual officials' actions to reveal the surprising extent to which administrative apparatuses were involved in the Nazi regime and its crimes."